Measuring Technology Maturity Operationalizing Information from Patents, Scientific Publications, and the Web - Albert, Till.; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2016)
Till Albert presents a machine learning based approach to harnessing information contained in big data from different media sources such as patents, scientific publications, or the internet. He shows how this information can be used for automated maturity evaluation of yet unknown technologies. Elaborate patent based indicators contain very useful information on technological aspects of maturity but lack for others such as social, economic, ecological, or political factors. The approach presented in this book is able to incorporate these other factors and provide a firm basis for robust technology maturity and speed of maturity evaluation. Contents Information Scattering in Different Text Media Identifying Text Media Suitable for Informetric Analyses and Deriving Relevant Indicator Values Using Machine Learning to Gauge the Maturity Classification Performance of a Set of Indicators Representation, Interpretation, and Utilization of Maturity Analysis Results Target Groups Researcher and students of Business Engineering, Informatics, and Mathematics Innovation Managers, Technology Managers, Business Intelligence Professionals, Future Researchers The Author Till Albert wrote this dissertation with Professor Martin G. Moehrle at the Institute of Project Management and Innovation (IPMI) of the University of Bremen. He now works in the area of data driven approaches to support innovation and technology management, such as patent analysis, scientometrics, webometrics, social network analysis, and combinations thereof. .
Information Scattering in Different Text Media -- Identifying Text Media Suitable for Informetric Analyses and Deriving Relevant Indicator Values -- Using Machine Learning to Gauge the Maturity Classification Performance of a Set of Indicators -- Representation, Interpretation, and Utilization of Maturity Analysis Results. .
Keywords: Business; Management; Industrial management; Operations research; Decision making; Business and Management; Innovation/Technology Management; Operation Research/Decision Theory; Electronic books